Grace and power : - Smith, Sally Bedell (Random House Audio, 2004)
Smith shows what it was really like to be inside the Kennedy White House. Drawing on interviews with scores of Kennedy intimates, including former lovers who have never spoken publicly before, and on private letters and personal papers, Smith sheds new light on the intricate relationships behind the purpose and political drama of his presidency.